(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This study examined differences between females and males in emotional intelligence (EI). The researchers conducted a test of association between EI and sex and on age in a sample of educational leadership doctoral students. Using a survey, the principal investigator collected measures on EI and other demographic information from the participants. The sample was made up of 36 educational leadership students (24 women and 12 men) attending a regional university located in the southern region of the United States. EI was evaluated by the Schutte Self-Report EI Test (Schutte et al., 1998), which evaluates four subscales (Perception of Emotion, Utilization of Emotion, Managing own Emotions, and Managing Others’ Emotions). When the researchers examined EI as a trait, they were unable to detect differences in EI based on gender and based on age. Additional research is needed to further understand EI in educational leadership doctoral students.